(untitled) (International Journal of Environmental Sciences, 2025)
Purpose: The major purpose is to assess and prioritize the influence of risk and uncertainty on project success along with significant factors that affect implementation of national priority projects. Design/Methodology/Approach: The study included both qualitative and quantitative methods, and 20 government funded national priority pride projects were chosen for the study using a census sampling technique. Mean and standard deviation were used to analyze factors, correlation was used to study the relationship between risk-uncertainty management and project success, and multiple regressions was performed to identify the impact followed relative importance index to assess the factors beyond risk and uncertainty. Findings/Result: The Risk Management is more important than uncertainty for construction project success. The statistical correlation between the components revealed that there was a significant relationship between Risk, Uncertainty, and Project Success. Risk is the strongest predictor and Uncertainty is the weakest predictor, with R value accounting for 58.6 percent, R square accounting for 34.4 percent, and adjusted R square accounting for 33.4 percent of overall deviation in Project Success, with the remaining percentage explained by other 52 factors. The factors affecting implementation of national priority construction projects, the main factors as reported by the survey respondents includes sequencing of work according to schedule, ineffective planning and scheduling of project by contractor, financing by contractor during construction, variation orders, hire of incompetent sub-contractor, poor supervision and poor site management, unusual low bid by contractors, budget allocation, design error due to unfamiliarity with the local conditions, environment and the materials and unavailability of competent staff. Originality/Value: The study contributes for Developing the Framework for Timely Completion of Government Funded Construction Projects of Nepal